HUBUNGAN LAMA PENGGUNAAN KB TERHADAP PERUBAHAN BERAT BADAN PADA AKSEPTOR KB HORMONAL DI PMB SORAYA TAHUN 2022 - Reni Saswita; Faulia Mauluddina (LPPM STIKes Mitra Adiguna, 2023)
Hormonal contraception is one of the most effective and reversible methods of contraception to prevent conception. Hormonal contraceptive methods are divided into 3, namely: pill contraceptive methods, injectable contraceptive methods, implant contraceptive methods. Hormonal contraception has side effects, namely menstrual depression, vaginal discharge, acne, and one of them is weight change, (Rahayu and Wijanarko, 2017). The purpose of this study was to determine the relationship between duration of use of family planning on changes in body weight in hormonal birth control acceptors. The scope of this research is reproductive health and family planning (KB). This study used a quantitative descriptive method with a cross sectional approach with a total sample of 93 people. The results obtained from the bivariate analysis of the chi-square statistical test showed that the value of p = 0.895 > a 0.05. The conclusion is that there is no relationship between the length of use of family planning and changes in body weight at BPM Soraya Palembang in 2022. Suggestions are that health workers/midwives can provide counseling that changes in weight are not only caused by length of use and type of contraception but can be caused by other factors such as pattern overeating, lack of activity, poor sleeping arrangements and excessive stress levels.